Exceptional field dependence of antiferromagnetic magnons in LiFePO4 - Werner, Johannes; Neef, Christoph; Koo, Changhyun; Ponomaryov, Alexey N.; Zvyagin, Sergei; Klingeler, Rüdiger (Physical review, 2021)
Low-energy magnon excitations in magnetoelectric LiFePO4 have been investigated by high-frequency-high-field electron spin resonance spectroscopy in magnetic fields up to B=58T and frequencies up to f=745GHz. For magnetic fields applied along the easy magnetic axis, the excitation gap softens and vanishes at the spin-flop field of BSF=32T before hardening again at higher fields. In addition, for B≲BSF we observe a resonance mode assigned to excitations due to Dzyaloshinskii-Moriya (DM) interactions, thereby evidencing a sizable DM interaction of ≈150μeV in LiFePO4. Both the magnetization and the excitations up to high magnetic fields are described in terms of a mean-field theory model which extends recent zero-field inelastic neutron scattering results. Our results imply that magnetic interactions as well as magnetic anisotropy have a sizable quadratic field dependence which we attribute to significant magnetostriction.
Im Titel die "4" ist tiefgestellt
Gesehen am 09.06.2021